Anaerobic Fungi Isolated From Bactrian Camel Rumen Contents Have Strong Lignocellulosic Bioconversion Potential - Xue, Yihan; Shen, Rui; Li, Yuqi; Sun, Zhanying; Sun, Xiaoni; Li, Fengming; Li, Xiaobin; Cheng, Yanfen; Zhu, Weiyun (Frontiers in Microbiology, 2022)
Abstract: This study aims to obtain anaerobic fungi from rumen and fecal samples and investigates their potential for lignocellulosic bioconversion. Multiple anaerobic strains were isolated from rumen contents (CR1 - CR21) and fecal samples (CF1 - CF10) of Bactrian camel by using the Hungate roll tube technique. After screening for fiber degradability, one strain each from rumen contents (Oontomyces sp. CR2) and feces (Piromyces sp. CF9) were compared with Pecoramyces sp. F1 (earlier isolated from goat rumen, having high CAZymes of GHs) for various fermentation and digestion parameters. The cultures were fermented with different substrates (reed, alfalfa stalk, broussonetia papyrifera leaves, melilotus officinalis) at 39 ℃ for 96 h. The Oontomyces sp. CR2 had the highest total gas and hydrogen production from most substrates in the in vitro rumen fermentation system, and also had the highest digestion of dry matter, neutral detergent fiber, acid detergent fiber and cellulose present in most substrates used. The isolated strains provided higher amounts of metabolites such as lactate, formate, acetate and ethanol in the in vitro rumen fermentation system, for use in various industrial applications. The results illustrated that anaerobic fungi isolated from Bactrian camel rumen contents (Oontomyces sp. CR2) has the highest lignocellulosic bioconversion potential, suggesting that the Bactrian camel rumen could be a good source for isolation of anaerobic fungi for industrial applications.